Cat owners' perception towards feline heart disease : a behavioural study - Lee, Yong Chong (2017)
Informed decisions to treat cat with heart diseases depend on awareness, knowledge and behaviour of owners. The purposes of this study were to (i) assess owner‟s awareness, and knowledge of feline heart diseases; (ii) determine barriers to treat cats with heart disease; (iii) examine relationship between attitude, subjective norms and perceived behavioural control towards intention to treat; and (iv) examine moderating role of empathic concern towards intention to treat feline that have been diagnosed with heart diseases. A total of 139 cats‟ pet owners participated in the survey. Data was collected using interviewer-assisted questionnaires on demographic, cat ownership, awareness of feline heart disease and intention to treat. Data were analysed using descriptive analysis and variance-based structural equation modeling. Majority of the respondents (49.6%) were aware that cats can have heart disease but, approximately 89.2% respondents did not understand about the disease and only 11.5% of them had good ability in identifying symptoms related to feline heart disease. The respondents showed that attitude, subjective norms and perceived behavioural control are positively associated with intention to treat even though cost was the main barrier (45.5%). Findings also indicated that empathic concern only moderates the relationship between perceived behavioural control and intention to treat. In conclusion, strategies and educational interventions are warranted to increase awareness and knowledge of cats‟ owners about feline heart disease.